«History Is on Our Side»: Historian as a Propagandist during the Great Patriotic War - Vitaly V. Tikhonov (Bylye Gody, 2012)
The article considers the role of historians in patriotic propaganda of the Great Patriotic War. Despite a number of researches, concerning this problem, it remains undeveloped. The work is based on both published documents and the ones, introduced for scientific use for the first time. The article characterizes the work of professional historians as lectors-propagandists both in rear areas and at the frontlines, describes development of propaganda organizational forms, discloses mechanisms of its functioning. The research covers the activities of such well-known historians, as E.V. Tarle, M.V. Nechkina, V.I. Shunkov, A.I. Yakovlev, S.V. Bakhrushin, etc. in wartime. Besides, the article considers the formation of allies’ positive image in history textbooks of Europe and America. Basing on the analysis of applying historic images in anti-German propaganda, the author comes to a conclusion it was efficient. What was specific about the wartime is that the weakening of ideological control caused the conflict among the historians, concerning historical facts and events interpretation. The conflict is shown on the example of historians meeting at Central Committee of the all-Russian Communist Party (Bolshevik) in 1944. Special attention is attached to V.I. Shunkov’s letters from the frontline, describing daily work of historian-propagandist in frontline conditions.